Remodeling of Discovery Inquiry Learning in Improving Students' Interest and Quality of Learning in Islamic Subjects in Junior High Schools: Remodelling Pembelajaran Discovery Inquiry Dalam Meningkatkan Minat Dan Kualitas Belajar Siswa Pada Mata Pelajaran Agama Islam di Sekolah Menengah Pertama - Bintang Anugrah Fahrurrozi; Isa Anshori (Academia Open, 2022)
This article aims to determine the interest and quality of student learning in Islamic subjects at SMPN 1 Gedangan if using the modeled discovery inquiry learning. In this study, it was conducted directly in the field with the research subjects of 8E grade students of SMPN 1 Gedangan. The results obtained from this study are the increase in students' interest in learning after doing the Discovery Inquiry learning modeling seen in the enthusiasm of students in learning and carrying out various tasks given by the teacher, up from low interest (68.18% students) and moderate (31.81% students). ), to be of high interest (100% of students). While the quality of learning can be judged from the scores achieved by students, the average increased from 6.05 to 9.2 which proves that this model is quite effective for the learning process.